(untitled) (Acta Scientiarum. Biological Sciences, 2013)
This study aimed to evaluate the temporal distribution of fish eggs and larvae in the Forquilha river (upper Uruguay river/Brazil) and its relationship with environmental variables. Ichthyoplankton and abiotic factors were sampled from September 2006 to August 2007. At the laboratory, samples were sorted and larvae were identified to the lowest possible taxonomic level. For data analysis we applied One-way Anova, Tukey’s test, Pearson correlation and PCA. In this study 200 eggs and 308 larvae were collected, showing differences in the temporal distribution and influence of abiotic factors. Larvae were identified in all stages of development, being distributed in three order and eight families. These results point that the lower portion of the Forquilha river is an important drift and nursery area for fish larvae of the upper Uruguay river. The breeding season for most species was greatly marked, between October and January, coinciding with the increase in temperature and decrease of the water flow. The response of reproductive intensity varies according to the environmental variables.